2019
DOI: 10.1149/2.1071913jes
|View full text |Cite
|
Sign up to set email alerts
|

The Sacrificial Protection of Steel by Zinc-Containing Sol-Gel Coatings

Abstract: The scanning vibrating electrode technique (SVET), electrochemical impedance spectroscopy, and salt spray testing are used to investigate the ability of Zn rich sol-gel coatings to provide sacrificial protection to carbon steel. Three types of coatings (containing either Zn powder, a coloured pigment, or both) are applied to steel. Intact coatings are shown to act as barrier layers through which electrolyte ingresses over time.Under conditions where the substrate is exposed by an artificial coating defect, SVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…[ 20,21 ] Since large pit formation is observed only in low pH solutions, it is concluded that the pH of the solution plays an active role in the propagation of the pits. A similar result has been reported by Wint et al [ 18 ]…”
Section: Experimental Results and Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…[ 20,21 ] Since large pit formation is observed only in low pH solutions, it is concluded that the pH of the solution plays an active role in the propagation of the pits. A similar result has been reported by Wint et al [ 18 ]…”
Section: Experimental Results and Analysissupporting
confidence: 91%
“…The pits formed in the acidic solution with 0.35 moL/L NaCl and neutral solution with 0.50 moL/L NaCl have many larger holes, with diameters in the range of 80 μm‐100 μm, in comparison to the pits formed from neutral solution with 0.35 moL/L NaCl. Similar results are discussed by Wang et al, [ 14 ] Wint et al, [ 18 ] and Miao et al [ 12 ] In a solution with higher Cl − concentration (0.50 moL/L NaCl), more intense pitting corrosion with larger pit growth was observed. The impedance spectroscopy of the neutral solution with the higher 0.50 moL/L NaCl concentration as confirmed through SEM images is consistent with the high impedance in the Nyquist plots due to the formation of corrosion products (Figure 10C).…”
Section: Experimental Results and Analysissupporting
confidence: 89%
See 3 more Smart Citations